Fatigue strength of 5Y-FSZ: glazing and polishing effects - de Carvalho, Ana Beatriz Gomes [UNESP] (2022)
Objective: The aim of this study was to evaluate the effect of four different finishing procedures on the fatigue strength of a fully stabilized zirconia (5Y-FSZ) material. Materials and methods: Disc-shaped specimens of a 5Y-FSZ (Katana UTML, Kuraray Noritake) were made (ISO 6872–2015), grinded with 600- and 1200-grit silicon carbide paper, sintered as recommended, and randomly assigned into four groups according to the finishing technique: C (control, as-sintered), P (polished with polishing rubbers), G (glaze application – powder/liquid technique), and PG (polished with polishing rubbers + glaze application – powder/liquid). Then fatigue strength (staircase method), X-ray diffraction (XRD), and scanning electron microscopy (SEM) analyses were performed. Results: The C group presented the lowest fatigue strength, while the PG group presented the highest. The P and G groups presented intermediate behavior, presenting similar statistical results. XRD showed similar crystalline phase patterns for all groups. SEM images revealed some changes in the zirconia surface, with the P group presenting some scratches on the surface, while the scratches in the PG group were filled with the glaze material. Conclusion: None of the techniques analyzed in this study impaired the fatigue strength of fully stabilized zirconia. Importantly, the polishing rubbers combined with glaze application (PG group) improved its fatigue strength. Clinical relevance: The polishing rubbers followed by glaze application improve the fatigue strength in ultra-translucent zirconia.